WRITING THE PROCEDURES TEXT USING DISCOVERY LEARNING METHOD IN HIGH SCHOOL STUDENTS - Jajang Munandar; Ika Mustika (IKIP Siliwangi, 2021)
The purpose of this study was to describe the development of teaching materials about the learning plan of writing procedural text with the discovery learning method in class XI SMA, the implementation of learning to write procedural texts with the discovery learning method in class XI SMA, and the assessment process of learning to write procedural texts using the discovery learning method in class XI. The subjects of this study were a class XI teacher and a class XI high school student. The things that are considered in this study are about the planning, implementation, and assessment process in learning to write procedural texts using the discovery learning method. The research data is in the form of observation and documentation. Data analysis using qualitative descriptive method. Based on the results of the study, it shows that the learning plan using the discovery learning method by the teacher has met the specified implementation standards. The success of a learning plan can be seen from the steps that are fulfilled according to the standard procedures for preparation of learning preparation using the discovery learning method. The implementation of learning can be categorized as successful in using the discovery learning method for learning to write procedural texts. The success of learning can be seen from the learning steps carried out by the teacher using the discovery learning method and student work results before and after using the discovery learning method in learning to write procedural text.